Thermally conductive and leakage-proof phase-change materials composed of dense graphene foam and paraffin for thermal management - Li, Hongling (2022)
Practical implementation of porous carbon-based composite phase-change materials (CPCMs) for heat dissipation in high-power-density electronics is usually limited by liquid leakage issues and unsatisfactory thermal conductivity resulting from their relatively low filler fraction and/or existence of interfacial thermal resistance between fillers. Therefore, development of shape-stable CPCMs with high thermal conductivity and large latent heat to avoid overheating of electronics remains challenging. Herein, graphene foams (GFs) with very high densities of up to 204 mg/cm3have been synthesized to act as interconnected porous networks of CPCMs. Notably, the obtained CPCM with a filler loading of 11.1 wt % preserves a high heat capacity (171.8 J/g) with a retention of 84.8% while showing a 22.6-fold enhancement in the thermal conductivity as compared to pure PCM (10.13 vs 0.43 W/m·K). A higher thermal conductivity of 14.29 W/m·K can be achieved by further increasing the filler loading to 17.7 wt %, which outperforms many of the previously reported CPCMs based on the interconnected porous carbon-based frameworks. Owing to the superior interconnected network structure of the dense GFs and the strong interconnection between them and PCM molecules, these CPCMs also exhibit leakage-proof shape stability and excellent thermal reliability (at least 100 cycles). Moreover, a state-of-the-art aluminum (Al) package based on the CPCM (filler loading: 11.1 wt %) possessing weight 60% less than its pure Al panel counterpart has been demonstrated to verify better heat transfer efficiency and more efficient phonon pathways of the CPCM composite than those of the pure PCM, which holds great promise for advanced thermal management of emerging applications in electronics.